Improving the Medium-Term Forecasting of Space Weather: A Big Picture Review From a Solar Observer's Perspective - Vourlidas, Angelos (Frontiers in Astronomy and Space Sciences, 2021)
Our scientific understanding of the solar drivers of Space Weather, i.e. Coronal Mass Ejections, flares, and solar energetic particles, has improved considerably in the last 20+ years thanks to a plethora of space missions and modeling advances. Yet, there has been no major breakthrough in assessing the geo-effectiveness of a given CME and associated phenomena, largely holding back actionable medium-term (up to 7 days) forecasting of Space Weather. Why is that? To search for answers, I first summarise the results of the last 20+ years of research on solar drivers by collecting lessons-learned and identifying paradigm shifts in our view of solar activity, always in relation to Space Weather concerns. Then, I review the state of the key observational-based quantities used in forecasting, which allows me to identify the choke points and research gaps that drive the current medium-term forecasting performance. Finally, I outline a path forward consisting of the measurements with the strongest potential to improve space weather forecasting horizon and robustness.